Fabrication of superhydrophobic caffeic acid/Fe@cotton fabric and its oil-water separation performance. (1st January 2019) - Zhou, Qingqing; Yan, Biaobiao; Xing, Tieling; Chen, Guoqiang
Graphical abstract: Highlights: A novel superhydrophobic caffeic acid/Fe@cotton fabric is fabricated. No fluorinated substances and organic solvents were added to the reaction system. The reaction conditions were mild, and the reaction was catalyzed by laccase. Caffeic acid/Fe@cotton fabric has excellent performance in oil-water separation. This method is versatile for many different substrates. Abstract: A superhydrophobic caffeic acid/Fe@cotton fabric (CfA/Fe@cotton fabric) was fabricated by a simple, high efficiency and environmentally friendly approach and the polymerization of caffeic acid was catalyzed by laccase. This superhydrophobic cotton fabric and caffeic acid/Fe hybrid particles (CfA/Fe) were characterized by scanning electron microscopy (SEM), atomic force microscope (AFM), X-ray diffraction (XRD) and so on. The results showed that the surface of cotton fiber was coated by CfA/Fe composite deposition film, and the ferrous ions can be reduced to zero valent iron particles with good crystal structure in the aging process of reaction. Compared with pristine cotton fabric, the superhydrophobic cotton fabric exhibited high water contact angle (CA) of about 158°. It could withstand various extreme conditions and 100 cycles of abrasion by friction tester without great changes of CA. In addition, CfA/Fe@cotton fabric had excellent self-cleaning and oil-water separation performance, and the oil separation efficiency was higher than 99%. Even after ten times of reuse, it still remained high efficiency separation ability. Moreover, this method has a certain degree of universality, the CfA/Fe can be deposited on many different substrates to form highly hydrophobic surfaces. This superhydrophobic cotton fabric has potential application value in oil-water separation, and this excellent preparation method also has broad application prospects.